Clinical And Operational Effectiveness Of Hemostatic And Clotting Aids For Bleeding Control In Emergency Medical Services: A Systematic Review (The Review of Diabetic Studies, 2025)
Uncontrolled hemorrhage remains one of the leading causes of preventable mortality in trauma and severe medical bleeding encountered by emergency medical services (EMS) in the prehospital environment. The time-sensitive and resource-limited nature of out-of-hospital care has accelerated the adoption of hemostatic and clotting aids as adjuncts to conventional interventions such as direct pressure, wound packing, tourniquets, and damage-control resuscitation protocols. This systematic review evaluates the clinical and operational effectiveness of topical and systemic clotting aids used by EMS providers for external and internal bleeding control. Evidence from civilian, tactical, and hybrid EMS systems indicates that modern topical dressings (kaolin- or chitosan-based) contribute to improved hemostasis rates, reduced time-to-bleeding control, enhanced first-attempt wound packing success, and overall stabilization of hemodynamic parameters prior to hospital transfer. Early prehospital administration of tranexamic acid (TXA) in major trauma also demonstrates potential mortality reduction and decreased need for massive transfusion in selected patient groups. Despite these benefits, evidence quality remains heterogeneous, with variable reporting of complications and limited randomized controlled trials addressing combined clinical and operational outcomes. Implementation-focused findings emphasize the importance of standardized protocols, high-fidelity training, logistical readiness, shelf-life governance, and operational feasibility to avoid delays in scene management. The review concludes that clotting aids improve prehospital bleeding control with acceptable safety profiles, yet further pragmatic and multicenter trials are needed to strengthen system-level recommendations for sustained integration in EMS bleeding pathways.